Method for improving interface performance and impact strength of fiber-reinforced metal laminated plate
By electroless copper plating on the surface of the titanium alloy plate and adding graphene nanoparticles to the polyether ether ketone matrix, the interfacial bonding ability and impact resistance of the fiber-reinforced metal laminated plate are enhanced, and the problem of insufficient interfacial bonding performance is solved, realizing the application of materials in high safety standards environments.
Patent Information
- Application Number
- CN202510426793.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-07
- Publication Date
- 2025-07-18
AI Technical Summary
The interface bonding and impact resistance of fiber reinforced metal laminates are insufficient, which limits its wide application in aerospace and other fields.
The surface of the titanium alloy plate is subjected to electroless copper plating, and graphene nanoparticles are added to the polyether ether ketone matrix. By alternately laying a mixed matrix of graphene nanoparticles and polyether ether ketone, the interface bonding ability between the fiber and the metal is enhanced.
Improves the interface bonding strength and impact resistance of fiber-reinforced metal laminates, simplifies the manufacturing process, reduces costs, and is suitable for use in high safety standards environments.
Smart Images

Figure CN120327077A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and particularly to a method for improving the interfacial performance and impact resistance of fiber-reinforced metal laminates. Background Art
[0002] With the rapid development of aerospace technology, the requirements for material properties of aircraft are increasing day by day. Composite materials, especially fiber-reinforced metal laminates, have become the first choice in the application of aircraft materials due to their excellent strength, high specific modulus, and strong temperature resistance. This material has not only been widely studied and developed, but also the proportion it occupies in the composition of aircraft materials continues to increase. The optimization and improvement of fiber-reinforced metal laminates, especially the innovation in structure and performance, are of great significance for meeting the high-standard requirements of the modern aerospace field. However, despite its many advantages, the interfacial bonding performance and impact resistance of fiber-reinforced metal laminates still have problems that limit their wider application. The interface between the fiber and the metal in the fiber-reinforced metal laminate is the weakest area of the entire structure. When subjected to impact loads, the failure of this area will cause various damage modes such as cracking, delamination, and debonding of the laminate. Therefore, it is of great significance to improve the interfacial performance and impact strength of fiber-reinforced metal laminates.
[0003] In the current engineering field, the interfacial performance of fiber-reinforced metal laminates mainly refers to the bonding strength of the matrix between the fiber and the metal, which directly affects the structural integrity and mechanical properties of the fiber-reinforced metal laminate. The impact resistance of fiber-reinforced metal laminates is an important design consideration in many key applications, especially in the aviation and military fields. When the laminate material encounters high-speed impact, fiber and matrix splitting will occur, and this damage will seriously weaken the structural strength and function of the laminate. Moreover, the weak bonding of the interface will directly affect the load transfer efficiency and structural integrity of the laminate, resulting in stress concentration, cracking and delamination, and a decrease in the energy absorption capacity during impact. In addition, the differences in thermal expansion coefficients, chemical and potential incompatibilities at the interface will also affect the stability and reliability of the laminate. Traditionally, improving the interface performance mainly relies on mechanical anchoring, chemical treatment, or adding bonding promoters. Physical methods such as acid treatment, anodic oxidation, or sandblasting are used to change the surface roughness of the metal, or chemical methods such as silane treatment are used to form chemical groups on the metal surface to enhance the bonding force of chemical bonds between the fiber and the metal. Although these methods have certain effects on improving the interfacial bonding ability of the laminate, they are highly dependent on processing conditions, the process is complex, and it is difficult to cope with impact and high-load environments.
[0004] Develop a new interface improvement technology that can not only effectively enhance the mechanical and chemical properties of the interface, but also durably resist the impact and the influence of harsh environments, while simplifying the manufacturing process and reducing costs. This is of great significance for improving the performance of fiber-reinforced metal laminates. Summary of the Invention
[0005] The object of the present invention is to overcome the deficiencies of the above-mentioned existing technologies and provide a method for improving the interface performance and impact resistance of fiber-reinforced metal laminates. This method can improve the bonding ability of the interface between the metal layer and the fiber layer, as well as improve the overall impact resistance of the fiber-reinforced metal laminates, which is of great significance for improving their performance.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] The present invention provides a method for improving the interface performance and impact resistance of fiber-reinforced metal laminates, and the method includes the following steps:
[0008] Step 1: Subject the titanium alloy plate to pickling, sensitization, and activation treatments in sequence, and then perform surface copper plating.
[0009] Step 2: Mix graphene nanoparticles with acetone and perform ultrasonic treatment Ⅰ to obtain a graphene nano-dispersion liquid, add polyether ether ketone, perform ultrasonic treatment Ⅱ, and then dry to obtain a mixed matrix of graphene and polyether ether ketone.
[0010] Step 3: Alternately lay the titanium alloy plate obtained in Step 1 and the fiber material, and evenly lay the mixed matrix of graphene nanoparticles and polyether ether ketone obtained in Step 2 between them, and ensure that the outermost layer is the titanium alloy plate. After laying, a laminate is formed.
[0011] Step 4: Cure the laminate obtained in Step 3 to obtain the fiber-reinforced metal laminate.
[0012] In the above-mentioned Step 1, take the titanium alloy plate for surface electroless copper plating treatment to obtain the treated titanium alloy plate. The copper layer on the surface of the treated titanium alloy plate can serve as an intermediate layer between the titanium alloy and the carbon fiber, improving the interface wettability and mechanical interlocking, thereby enhancing the interface bonding strength.
[0013] In the above technical solution, further, the titanium alloy plate is a TC4 titanium alloy plate with a thickness of 0.5 - 1 mm;
[0014] The fiber material is carbon fiber or glass fiber with a thickness of 0.25 - 0.3 mm.
[0015] In the above technical solution, in Step 1, it specifically includes the following steps:
[0016] (1) Acid-treat the titanium alloy plate with sulfuric acid at an acid-treatment temperature of 140 °C for 5 - 7 min, and then wash it with deionized water;
[0017] (2) Immerse the acid-treated titanium alloy plate in a silane coupling agent solution for sensitization treatment at a sensitization temperature of 25 - 30 °C for 30 - 40 min;
[0018] (3) Immerse the sensitized titanium alloy plate in a mixed solution of palladium chloride and hydrochloric acid for 30 - 40 min for activation treatment, wash it with deionized water, and dry it to obtain a pretreated titanium alloy plate;
[0019] (4) Immerse the pretreated titanium alloy plate in an electroless copper plating solution, soak it at 50 - 60 °C for 45 - 60 min, then wash it with deionized water, dry it, and then dry it at 130 - 150 °C for 40 - 60 min.
[0020] In the above technical solution, further, in step (1), the volume fraction of the sulfuric acid is 40% - 50%.
[0021] In the above technical solution, further, in step (2), in the silane coupling agent solution, the volume fraction of the silane coupling agent is 1% - 3%, and pH = 4 - 4.5.
[0022] In the above technical solution, further, in step (3), in the mixed solution of palladium chloride and hydrochloric acid, the concentration of palladium chloride is 0.2 - 0.25 g / L, and the volume fraction of hydrochloric acid is 0.5% - 1%;
[0023] The drying temperature is 110 - 120 °C, and the drying time is 30 - 40 min.
[0024] In the above technical solution, further, in step (4), the electroless copper plating solution is composed of 15 g / L CuSO4, 20 g / L KNaC4H4O6, 15 g / L EDTA, and 15 g / L NaH2PO2, and the pH of the electroless copper plating solution is 13;
[0025] The drying temperature is 130 - 150 °C, and the drying time is 40 - 60 min.
[0026] In the above technical solution, further, in step 2, the mass ratio of the graphene nanoparticles in the mixed matrix is 0.25% - 0.75%.
[0027] In the above technical solution, further, the curing process is: raise the temperature to 385 - 390 °C under a pressure of 0.2 - 0.5 MPa, and then increase the pressure to 4 - 5 MPa and maintain it for 20 - 30 min.
[0028] Advantages of the present invention:
[0029] 1. In the present invention, graphene nanoparticles are added to the polyetheretherketone (PEEK) matrix to improve the interfacial bonding ability of the fiber-reinforced metal laminate, improve the adhesion between the fiber and the metal, and increase the overall structural integrity and durability of the composite material.
[0030] 2. In the present invention, copper is electrolessly plated on the surface of the titanium alloy plate, and the surface copper layer can improve the wettability and mechanical interlocking of the interface, and enhance the bonding strength between the titanium alloy layer and the fiber layer.
[0031] 3. The fiber-reinforced metal laminate prepared by the present invention improves the impact resistance of the material by optimizing the interface layer, and is suitable for use in an environment with high safety standards.
[0032] 4. The preparation method of the present invention is simple and effective, without a complex operation process, and can be widely applied. Description of the Drawings
[0033] Figure 1 It is a flowchart of the Charpy impact experiment of the fiber-reinforced metal laminate of the present invention, wherein:
[0034] 1. Fiber-reinforced metal laminate, 2. Mixed matrix of graphene nanoparticles and polyetheretherketone, 3. Charpy impact experiment punch, 4. Mechanical fixture;
[0035] Figure 2 It is the absorbed energy and impact resistance strength of the fiber-reinforced metal laminate prepared in Examples 1-5 and Comparative Example 1 of the present invention after Charpy impact, where a is the absorbed energy and b is the impact resistance strength. Detailed Embodiments
[0036] The present invention will be further described in detail below with reference to the embodiments.
[0037] Unless otherwise specified, the materials used in the embodiments of the present invention can be obtained through commercial channels or prepared by conventional methods well-known to those skilled in the art.
[0038] Example 1
[0039] A method for improving the interfacial performance and impact resistance strength of a fiber-reinforced metal laminate specifically includes the following steps:
[0040] Step 1: The titanium alloy plate is sequentially pickled, sensitized, and activated, and then surface copper plating is carried out, specifically including the following steps:
[0041] (1) The TC4 titanium alloy plate (with a thickness of 0.5 mm) is acid-treated, wherein it is treated with 40% concentrated sulfuric acid at 140°C for 5 minutes, and then washed with deionized water;
[0042] (2) Immerse the acid-treated TC4 titanium alloy plate in a silane coupling agent solution, soak at 30 °C for 30 min for sensitization treatment, where the silane coupling agent solution is KH550 with a volume fraction of 3% and pH = 4.5;
[0043] (3) Immerse the sensitized TC4 titanium alloy plate in a mixed solution of palladium chloride and hydrochloric acid for 30 min for sensitization treatment, where the content of palladium chloride and the volume fraction of hydrochloric acid are 0.25 g / L and 1% respectively, then wash with deionized water and dry at 110 °C for 30 min to obtain the pretreated TC4 titanium alloy plate;
[0044] (4) Immerse the pretreated TC4 titanium alloy plate in an electroless copper plating solution, soak at 60 °C for 60 min, where the electroless copper plating solution is composed of 15 g / L CuSO4, 20 g / L KNaC4H4O6, 15 g / L EDTA, and 15 g / L NaH2PO2, pH = 13, then wash the surface of the titanium alloy plate after copper plating with deionized water and dry at 150 °C for 60 min;
[0045] Step 2: Mix graphene nanoparticles with acetone, ultrasonically treat at 30 °C for 6 h to completely disperse the graphene nanoparticles in the acetone solution to obtain a graphene nanoparticle dispersion, add polyetheretherketone (PEEK), ultrasonically treat at 30 °C for 3 h to fully mix the polyetheretherketone with the graphene nanoparticles, then first dry at 80 °C for 2 - 3 h to remove the excess acetone solution, and then raise the temperature to 150 °C and dry for 1 h to remove the moisture to obtain a mixed matrix of graphene nanoparticles and polyetheretherketone, where the mass ratio of graphene nanoparticles in the mixed matrix is 0.5%;
[0046] Step 3: Alternately lay the copper-plated titanium alloy plate and the T300 - 3K bidirectional woven carbon fiber (with a thickness of 0.3 mm), and evenly lay the mixed matrix of graphene nanoparticles and polyetheretherketone between them. Specifically: first lay the copper-plated titanium alloy plate, then lay the mixed matrix of graphene nanoparticles and polyetheretherketone on the copper-plated titanium alloy plate, then lay the carbon fiber on the mixed matrix, lay the mixed matrix on the carbon fiber, and finally lay the copper-plated titanium alloy plate on the mixed matrix. After laying, a laminate is formed. The number of layers of the laminate is three, including 2 layers of titanium alloy plates and 1 layer of carbon fiber layer;
[0047] Step 4: Cure the laminate. The curing process is: raise the temperature to 390 °C under a pressure of 0.2 MPa, then increase the pressure to 5 MPa and maintain for 30 min to obtain a fiber-reinforced metal laminate.
[0048] Example 2
[0049] The same preparation method as in Example 1 was used, except that in Step 2, the mass ratio of graphene nanoparticles in the mixed matrix was 0.25%.
[0050] Example 3
[0051] The same preparation method as in Example 1 was used, except that in Step 2, the mass ratio of graphene nanoparticles in the mixed matrix was 0.75%.
[0052] Comparative Example 1
[0053] Step 1: The titanium alloy plate was successively pickled, sensitized, and activated, and then copper plating was carried out on the surface, specifically including the following steps:
[0054] (1) The TC4 titanium alloy plate (with a thickness of 0.5 mm) was acid-treated, where 40% concentrated sulfuric acid was used at 140 °C for 5 min, and then it was washed with deionized water;
[0055] (2) The acid-treated TC4 titanium alloy plate was immersed in a silane coupling agent solution and soaked at 30 °C for 30 min for sensitization treatment, where the silane coupling agent solution was 3% by volume of KH550 and pH = 4.5;
[0056] (3) The sensitized TC4 titanium alloy plate was immersed in a mixed solution of palladium chloride and hydrochloric acid for 30 min for sensitization treatment, where the content of palladium chloride and the volume fraction of hydrochloric acid were 0.25 g / L and 1% respectively, and then it was washed with deionized water and dried at 110 °C for 30 min to obtain the pretreated TC4 titanium alloy plate;
[0057] (4) The pretreated TC4 titanium alloy plate was immersed in an electroless copper plating solution and soaked at 60 °C for 60 min. The electroless copper plating solution was composed of 15 g / L CuSO4, 20 g / L KNaC4H4O6, 15 g / L EDTA, and 15 g / L NaH2PO2, with pH = 13. Then, the titanium alloy plate after surface copper plating was washed with deionized water and dried at 150 °C for 60 min;
[0058] Step 2: The copper-plated titanium alloy plate and the T300-3K bidirectional woven carbon fiber (with a thickness of 0.3 mm) were alternately laid, and a polyether ether ketone matrix was evenly laid between them. Specifically: first, the copper-plated titanium alloy plate was laid, then the polyether ether ketone matrix was laid on the copper-plated titanium alloy plate, then the carbon fiber was laid on the mixed matrix, then the polyether ether ketone matrix was laid on the carbon fiber, and finally the copper-plated titanium alloy plate was laid on the polyether ether ketone matrix. After laying, a laminate was formed;
[0059] Step 3: Cure the laminate, and the curing process is as follows: Raise the temperature to 390°C under a pressure of 0.2 MPa, then increase the pressure to 5 MPa and hold for 30 min to obtain the fiber-reinforced metal laminate.
[0060] Comparative Example 2
[0061] The same preparation method as in Example 1 was used, except that in Step 2, the mass ratio of graphene nanoparticles in the mixed matrix was 1%.
[0062] Comparative Example 3
[0063] The same preparation method as in Example 1 was used, except that in Step 2, the mass ratio of graphene nanoparticles in the mixed matrix was 1.5%.
[0064] Test Example 1
[0065] An impact load was applied to the fiber-reinforced metal laminates prepared in Examples 1-3 and Comparative Examples 1-3 according to the ISO 197-1 standard. The specimen size was 50×10×1.5 mm. As Figure 1 shown, place the fiber-reinforced metal laminate 1 on the mechanical fixture 4, apply an initial energy to the Charpy impact test punch 3. In this example, the initial energy was 15 J. When the impact was completed, record the absorbed energy and impact resistance of the fiber-reinforced metal laminate 1. The test results are as Figure 2 shown.
[0066] It can be seen from Figure 2 that the absorbed energy and impact strength of Example 1 under impact were the highest, reaching 11.387 J and 832.89 kJ / m 2 . The absorbed energy and impact strength of Example 1 increased by 2.725 J and 166.58 kJ / m respectively compared with Comparative Example 1 2 . The impact performance of Example 2 and Example 1 increased with the increase of graphene. Since graphene forms a nano-network structure in the PEEK matrix, it can better resist external impact and load. However, the impact performance of Example 3, Comparative Example 2 and Comparative Example 3 decreased with the increase of graphene. Because the addition amount of graphene was too large, resulting in the aggregation and stacking of graphene inside the fiber-reinforced metal laminate. And the aggregation and stacking of graphene will cause stress concentration and premature failure when subjected to impact, thus reducing the impact resistance of the fiber-reinforced metal laminate.
[0067] The present invention uses electroless copper plating on the surface of titanium alloy. The obtained copper layer can serve as a transition layer between the metal layer and the fiber layer, improving the wettability and mechanical interlocking of the interface and enhancing the interfacial bonding ability between the two. Moreover, the copper layer can help adjust the difference in thermal expansion coefficients of different materials in the composite material, reduce the internal stress caused by temperature changes, and enhance the thermal stability of the material. In the present invention, the matrix of the fiber-reinforced metal laminate adopts a thermoplastic material, which can serve for a long time at 250 °C and can be recycled and reused, meeting the requirements of environmental protection. The present invention modifies the thermoplastic matrix with graphene nanoparticles to improve its impact resistance. And the interfacial bonding between carbon fiber and the thermoplastic matrix is improved by increasing the surface area and providing more bonding points, thereby enhancing the overall structural integrity of the material. The present invention provides a method for improving the interface and impact strength of fiber-reinforced metal laminates, enhancing the interfacial bonding ability and impact strength of fiber-reinforced metal laminates, which has important innovative significance and will have great application potential in the fields of automobiles or aviation, etc.
[0068] The above embodiments are only preferred embodiments of the present invention and do not limit the implementation manners. The protection scope of the present invention shall be subject to the scope defined by the claims. Other different forms of changes or variations can be made on the basis of the above description. The obvious changes or variations derived therefrom still fall within the protection scope of the present invention.
Claims
1. A method for improving the interfacial properties and impact resistance of fiber-reinforced metal laminates, characterized in that The method includes the following steps: Step 1: Sequentially subject the titanium alloy plate to pickling, sensitization, and activation treatments, and then perform surface copper plating; Step 2: Mix graphene nanoparticles with acetone, perform ultrasonic treatment Ⅰ to obtain a graphene nanoparticle dispersion, add polyetheretherketone, perform ultrasonic treatment Ⅱ, and dry to obtain a mixed matrix of graphene nanoparticles and polyetheretherketone; Step 3: Alternately lay the titanium alloy plate obtained in Step 1 and the fiber material, and evenly lay the mixed matrix of graphene nanoparticles and polyetheretherketone obtained in Step 2 between them, ensuring that the outermost layer is the titanium alloy plate. After laying, a laminate is formed; Step 4: Cure the laminate obtained in Step 3 to obtain the fiber-reinforced metal laminate.
2. The method according to claim 1, characterized in that, The titanium alloy plate is a TC4 titanium alloy plate with a thickness of 0.5 - 1 mm; The fiber material is carbon fiber or glass fiber with a thickness of 0.25 - 0.3 mm.
3. The method according to claim 1, wherein In Step 1, it specifically includes the following steps: (1) Acid-treat the titanium alloy plate with sulfuric acid. The acid treatment temperature is 140 °C, and the acid treatment time is 5 - 7 min. Then wash with deionized water; (2) Immerse the acid-treated titanium alloy plate in a silane coupling agent solution for sensitization treatment. The sensitization treatment temperature is 25 - 30 °C, and the sensitization treatment time is 30 - 40 min; (3) Immerse the sensitized titanium alloy plate in a mixed solution of palladium chloride and hydrochloric acid for 30 - 40 min for activation treatment, wash with deionized water, and dry to obtain a pretreated titanium alloy plate; (4) Immerse the pretreated titanium alloy plate in an electroless copper plating solution, soak at 50 - 60 °C for 45 - 60 min, then wash with deionized water, dry, and then dry at 130 - 150 °C for 40 - 60 min.
4. The method according to claim 3, wherein In Step (1), the volume fraction of the sulfuric acid is 40% - 50%.
5. The method according to claim 3, wherein In Step (2), in the silane coupling agent solution, the volume fraction of the silane coupling agent is 1% - 3%, and PH = 4 - 4.
5.
6. The method according to claim 3, wherein In Step (3), in the mixed solution of palladium chloride and hydrochloric acid, the concentration of palladium chloride is 0.2 - 0.25 g / L, and the volume fraction of hydrochloric acid is 0.5% - 1%; The drying temperature is 110 - 120 °C, and the drying time is 30 - 40 min.
7. The method according to claim 3, characterized in that In Step (4), the electroless copper plating solution is composed of 15 g / L CuSO4, 20 g / L KNaC4H4O6, 15 g / L EDTA, and 15 g / L NaH2PO2, and the PH of the electroless copper plating solution is 13; The drying temperature is 130 - 150 °C, and the drying time is 40 - 60 min.
8. The method according to claim 1, wherein In Step 2, the mass ratio of the graphene nanoparticles in the mixed matrix is 0.25% - 0.75%.
9. The method according to claim 1, characterized in that, The curing process is: Raise the temperature to 385 - 390 °C under a pressure of 0.2 - 0.5 MPa, and then increase the pressure to 4 - 5 MPa and maintain it for 20 - 30 min.
Citation Information
Patent Citations
Metal coating plumbago composite material and method of producing the same
CN101508596A
Carbon fiber cloth-titanium alloy composite material and preparation method thereof
CN102936706A
Preparing method of thermoplastic resin matrix carbon fiber-titanium / titanium alloy laminate plate
CN107283871A
Method for preparing graphene reinforced titanium-based composite material by means of microwave sintering
CN111041275A
Titanium-carbon fiber-titanium sandwich type composite material and preparation method thereof
CN113665188A